TRIM18-Regulated STAT3 Signaling Pathway via PTP1B Promotes Renal Epithelial–Mesenchymal Transition, Inflammation, and Fibrosis in Diabetic Kidney Disease - Chen, Qi; Gao, Chan; Wang, Ming; Fei, Xiao; Zhao, Ning (Frontiers in Physiology, 2021)
Diabetic kidney disease (DKD) has become a key cause of end-stage renal disease worldwide. Inflammation and fibrosis have been shown to play important roles in the pathogenesis of DKD. MID1, also known as TRIM18, is an E3 ubiquitin ligase of the tripartite motif (TRIM) subfamily of RING-containing proteins and increased in renal tubule in patients with DKD. However, the function and molecular mechanism of TRIM18 in DKD remain unexplored. Herein we report that TRIM18 expression levels were increased in patients with DKD. An animal study confirms that TRIM18 is involved in kidney injury and fibrosis in diabetic mice. TRIM18 knockdown inhibits high glucose (HG)-induced epithelial–mesenchymal transition (EMT), inflammation, and fibrosis of HK-2 cells. This is accompanied by decreased levels of tumor necrosis factor alpha, interleukin-6, hydroxyproline (Hyp), connective tissue growth factor, and α-smooth muscle actin. Additionally, TRIM18 knockdown inhibits HG-induced increase in the phosphorylated-/total signal transducer and activator of transcription (STAT3). Treatment with niclosamide (STAT3 inhibitor) or protein tyrosine phosphatase-1B (PTP1B) overexpression blocked the TRIM18 induced EMT, inflammation and fibrosis. Co-immunoprecipitation and Western blot assays showed that TRIM18 promoted the ubiquitination of PTP1B. These findings highlight the importance of the TRIM18/PTP1B/STAT3 signaling pathway in DKD and can help in the development of new therapeutics for DKD treatment.